Seismic performance-based design optimization of 2D steel chevron-braced frames using ACO algorithm and nonlinear pushover analysis - Faghirnejad, Saba; Kontoni, Denise-Penelope N.; Camp, Charles V.; Ghasemi, Mohammad Reza; Mohammadi Khoramabadi, Maryam (Structural and multidisciplinary optimization, 2025)
Nonlinear pushover analysis involves an extremely iterative process necessary for satisfying the design requirements of performance-based codes. This analysis also demands significant computational resources and advanced scientific efforts. In this study, we introduce a computer-based method for 2D-braced steel buildings that incorporates pushover analysis, optimization techniques, and optimality criteria methods to automatically design the pushover drift performance. An ant colony metaheuristic optimization algorithm is employed to achieve optimal performance-based designs for columns, chevron braces, and beams in steel moment frames. The initial phase includes implementing optimization codes in MATLAB and OpenSees for conducting the nonlinear static analysis of the 2D-braced steel frames. Several optimal configurations are produced for each brace and frame by addressing the nonlinear optimization problem. In the second step, a nonlinear pushover analysis is conducted in accordance with the provisions of the FEMA 356 code. This analysis takes into account constraints on relative displacement and plastic hinge rotation to ensure that the structure achieves the specified performance levels. Finally, the third step involves selecting the optimal design for each frame and subsequently plotting the pushover, drift and convergence curves for each frame and performance levels. This selection process ultimately aims to satisfy the criteria of performance-based design, including life safety, collapse prevention, and immediate occupancy, while minimizing the total weight for three 2D steel chevron frames: a 5-story, a 9-story, and a 13-story configuration.